Treatment persistence, hypoglycaemia and clinical outcomes in type 2 diabetes patients with dipeptidyl peptidase‐4 inhibitors and sulphonylureas: a primary care database analysis. Issue 1 (9th September 2012) - Rathmann, W.; Kostev, K.; Gruenberger, J. B.; Dworak, M.; Bader, G.; Giani, G.
Abstract Aims To investigate therapy persistence, frequency of hypoglycaemia and macrovascular outcomes among type 2 diabetes patients with dipeptidyl peptidase‐4 (DPP‐4) inhibitors (DPP‐4) and sulphonylureas (SU). Methods Data from 19 184 DPP‐4 (mean age: 64 years; 56% males) and 31 110 SU users (69 years; 51%) with new prescriptions (index date), without additional antidiabetics except metformin, in 1201 general practises in Germany were analysed. Therapy discontinuation (prescription gap >90 days), hypoglycaemia [International Classification of Diseases (ICD‐10)] and macrovascular outcomes (ICD‐10) (2‐year follow‐up) were compared adjusting for age, sex, diabetes duration, metformin, previous hypoglycaemia, health insurance, hypertension, hyperlipidaemia, antihypertensives, lipid‐lowering and antithrombotic drugs, microvascular complications and Charlson co‐morbidity score using logistic or Cox regression models. Results Two years after index date, DDP‐4 (non‐persistence: 39%) were associated with a lower risk of discontinuation compared to SU (49%) [adjusted hazard ratio (HR): 0.74; 95% confidence interval (CI): 0.71–0.76]. Hypoglycaemias (≥1) were documented in 0.18% patients with DPP‐4 and in 1.00% with SU [odds ratio (OR): 0.21; 95%CI: 0.08–0.57]. Hypoglycaemias were significantly associated with incident macrovascular complications (HR: 1.6; 95% CI: 1.1–2.2). Risk of macrovascular events was 26% lower in DPP‐4 than in SU users. Conclusions Lack of persistence with antidiabetic therapy is frequently found in primary care patients. DPP‐4 was associated with lower therapy discontinuation and a fivefold reduced frequency of patients with hypoglycaemia compared to SU. The low absolute numbers of hypoglycaemias are most likely due to the fact that only severe events were documented. DPP‐4 treatment was associated with reduced incidence of macrovascular events relative to SU in type 2 diabetes patients in primary care practises.